Multi-aspect Analysis of Rice Sustainability in the Improvement of Rice Production in North Sumatra Province, Indonesia - Lindawati, Lindawati; Zulfida, Ida; Nasution, Siti Khadijah Hidayati; Handayani, Sri (Universitas Panji Sakti, 2024)
North Sumatra's food security highly depends on rice supply from rice fields in rice-producing districts, namely Deli Serdang, Serdang Bedagai and Simalungun. The decrease in rice field area impacts the North Sumatra region's rice supply. This research aims to analyze the sustainability status and sensitive factors that cause the sustainability of rice fields based on economic, ecological, social, technological, legal, and institutional dimensions using Multi-aspect Sustainability Analysis software. The research results show that, in aggregate, the sustainability of rice fields is in the quite good category with a score of 62. Apart from the less sustainable economic aspect with a score of 59.09, there are four other aspects, such as environmental, social, infrastructure and technology, laws and regulations, and institutions, declared sustainable with a score greater than 62. The research also found 15 sensitive key factors that can improve the sustainability status of rice fields in North Sumatra to become very sustainable